การมีส่วนร่วมของสภาผู้ชมและผู้ฟังรายการที่มีต่อ องค์การกระจายเสียงและแพร่ภาพสาธารณะ แห่งประเทศไทย - กรรณิการ์ ชมภูศรี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this qualitative study is to explore participation of the Audience Council in the Thai Public Broadcasting Service (Thai PBS) and its effects. Documentary study, participant observation and in-depth interview are the main collecting data methods. The key informants are: ten purposively selected members of the Audience Council, three members of Board of Governor, one member of Executive Board, and four staffs of Thai PBS. The research was conducted from May to December 2014. The study shows that the Audience Council that works on behalf of viewers and listeners has performed its five legally assigned tasks completely: 1) monitoring the broadcasting programs, sharing the ideas among the members and formulating the agenda of the council meeting 2) arranging the participation process to collect feedbacks and suggestions from audiences in all regions of the country every three months 3) setting up and extending the "Friend of Thai PBS Network" throughout the country 4) preparing quarterly report composed of the comments and suggestions of audiences in all regions of the country 5) reporting the experience gained from annual working and providing recommendations to the Board of Governor and the Executive Board. The study reveals that the Audience Council emphasized working on the tasks 2 and 4 since they involves the proposal for program content improvement, the proposal for implementation adjustment and the policy recommendation. Participation of the Audience Council affects the Thai PBS in three folds. First, effects on policy: the proposal of the Audience Council corresponds to the policy of Thai PBS, namely participation of members, a sense of belonging among the public, access to public media, policy on news reporting and programs, policy on database of educational media, and personnel management policy. Second, effects on implementation: News programs have been changed to be more indepth. News reporting from locality have been increased in time of broadcasting. Regional center for news reporting has been set up. Citizen journalists have been trained to improve their contents and methods of presentation. The capability and identity of Thai PBS's staffs have been built up to reflect more vividly its position of public media. This is also the case for the participation of a variety of organizations from every sector. Third, effects on program format and content: The theme of Thai PBS programs have been guided by the Audience Council. These themes are anti-corruption, environment related disaster, ASEAN Economic Community, political and social reform, and deep south crisis. These contents had been presented to public through news programs and other programs related to news. The important finding is that participation of the Audience Council opens a new dimension of cooperation between active audience and national mass media. This opens up space where citizen can actively participate in mass media affairs. It, therefore, reflects participatory democracy in mass media. This participation has four characteristics: participation as message receiver, participation as operator, participation as policy maker, and participation in evaluation process. The only exception is participation in decision making. This high level of consciousness in participation and a sense of belonging leading to high expectation towards the role of public media would easily put the TPBS under pressure and create a condition of "interference in media ". This study suggests that the Audience Council, the Board of Governor and the Executive Board have to learn to working together, to cooperate horizontally using two-way communication, and respect the role of each partner in moving forward Thai PBS to reach its vision: the high quality public media institution that strives to promote a just and an informed society. Moreover, new approaches to gather comments and suggestions from viewers and listeners and develop high quality proposal should be continuously developed.